Placebo-driven clinical trials of yeast-derived β-(1-3) glucan in children with chronic respiratory problems - Vetvicka, Vaclav; Richter, Josef; Svozil, Vladimir; Rajnohová Dobiášová, Lucie; Král, Vlastimil (Annals of translational medicine, 2013)
BACKGROUND: The role of glucan in stimulation of immune reactions has been studied for several decades. In this report we focused on the effects of orally administered glucan in children with chronic respiratory problems. MATERIALS AND METHODS: We measured the levels of albumin, lysozyme and CRP in saliva of 40 children aged 8-12 years and evaluate the effects of 100 mg/d oral dose of glucan. RESULTS: We found a significant increase in production of changes in production of lysozyme and CRP in glucan-treated children. In addition, a strong improvement in general conditions was found. CONCLUSIONS: Short-term oral application of natural immunomodulator β-glucan stimulated mucosal immunity of children with chronic respiratory problems.
Keywords: lysozyme; mucosal immunity; children; Glucan; saliva